Genetic divergence and path co-efficient analysis in kala zeera (Bunium persicum Boiss. Fedtsch.) - M Sharma, S K Gupta, S Kumar, (Journal of Spices and Aromatic Crops, 2013)
Genetic variation and path coefficient analysis was carried out in seven genotypes of kala zeera (Bunium persicum). The genotypic, phenotypic and environmental correlations were calculated by applying the technique of variance-covariance analysis in which total variability was split into treatments, replication and error. The results indicated that the values of genotypic correlation coefficients were higher in general, than the phenotypic ones. Number of seed umbellet-1, number of seed plant-1, umbel diameter, number of secondary and tertiary branches plant-1, number of umbellets umbel-1 and number of seed umbel-1 recorded significant positive association with seed yield ha-1 at the genotypic level. However, at phenotypic level, number of primary, secondary and tertiary branches plant-1, umbel diameter, number of umbellets umbel-1, number of umbels plant-1, number of seed umbellet-1, number of seed umbel-1, number of seed plant-1 and 1000 seed weight were strongly associated with seed yield ha-1. The characters such as number of umbels plant-1, number of seed umbel-1, umbel diameter and number of primary branches plant-1 contributed directly as well as indirectly in the expression of seed yield ha-1. Residual effects was found to be significantly low (0.055) indicating that the number of primary branches plant-1 was the most reliable trait for improving the seed yield of Bunium persicum through selection.